1993
DOI: 10.1152/ajprenal.1993.264.3.f523
|View full text |Cite
|
Sign up to set email alerts
|

Increased soluble EGF after ischemia is accompanied by a decrease in membrane-associated precursors

Abstract: We have characterized the distribution of immunoreactive epidermal growth factor (irEGF) in control and ischemia-injured rat kidneys. Kidneys that had undergone ischemic injury contained levels of soluble irEGF that were six times those of uninjured kidneys. The predominant forms of soluble irEGF were native and des-Arg-epidermal growth factor (EGF), both of which are biologically active. Crude membrane fractions from whole kidneys were solubilized in Triton X-100 and tested for irEGF. Amounts of irEGF were sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 1 publication
3
14
3
Order By: Relevance
“…This antibody allowed us to demonstrate the presence of immunoreactive EGF in the exocrine rat lacrimal gland. In this tissue EGF was shown to be stored as its high molecular weight membrane-anchored precursor as already shown in kidney (12,36,37,39). Immunoreactive rat EGF is also present in corresponding secretory fluids, i.e.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This antibody allowed us to demonstrate the presence of immunoreactive EGF in the exocrine rat lacrimal gland. In this tissue EGF was shown to be stored as its high molecular weight membrane-anchored precursor as already shown in kidney (12,36,37,39). Immunoreactive rat EGF is also present in corresponding secretory fluids, i.e.…”
Section: Discussionsupporting
confidence: 64%
“…In order to lead to the ultimate, mature 6-kDa form of the molecule, the ectodomain needs to be further maturated in the extracellular medium. It has already been shown that, in vitro, mature EGF could be released from its precursor through the action of different type of proteases; acidic protease such as pepsin (36) or serine-proteases such as trypsin (22,39,41) and plasmin (44). Moreover, membrane fractions of both kidney (45,46) and mammary gland (47) contain a membrane-bound proteolytic activity that colocalized with pro-EGF and released soluble EGF from its membraneassociated precursor.…”
Section: Epidermal Growth Factor (Egf)mentioning
confidence: 99%
“…EGF production in the adult mouse kidney has been localized to the thick ascending limb/ distal convoluted tubule (33). After either ischemic or nephrotoxic injury, both preproEGF mRNA levels and urinary EGF levels decrease and remain significantly depressed for up to 7 d (28,34), although it has been reported that there is increased processing of preproEGF to its soluble, active form in response to acute ischemic renal injury (35). In addition, HB-EGF expression has been shown to increase significantly in rat kidney in response to acute tubular injury induced by mercuric chloride, ischemia, aminoglycosides, or folic acid (4 -6).…”
Section: Discussionmentioning
confidence: 99%
“…In rat kidneys with I/R injury, EGF immunoreactivity detected by immunohistochemical study decreases [27, 28, 29]but concentration of mature EGF rose 7- to 10-fold [21]. At the mRNA level, the EGF precursor [30]and prepro EGF mRNA [31]are decreased during renal tubular regeneration. Thus, it is suggested that that mature EGF protein is present in renal tubular cells as preformed form, and released when kidney is damaged by I/R injury.…”
Section: Discussionmentioning
confidence: 99%